Transcriptional control of the bovine leukemia virus genome: role and characterization of a non-immunoglobulin plasma protein from bovine leukemia virus-infected cattle. - Gupta, P (1984)
Using cloned bovine leukemia virus (BLV) DNA as a probe in the dot blot hybridization technique, we demonstrated that the expression of the BLV genome in infected lymphocytes is blocked in vivo at the transcriptional level. This blocking effect is due to a non-immunoglobulin protein present in the plasma but not in the serum of BLV-infected cattle. The plasma BLV-blocking protein also blocks the expression of the BLV genome in fibroblast cells of bovine and nonbovine origin infected with BLV in vitro. The plasma BLV-blocking factor has no inhibitory effect on the expression of Rauscher murine leukemia virus and feline leukemia virus in monolayer culture. The plasma BLV-blocking factor is not an interferon molecule. As determined by gel filtration chromatography, the plasma BLV-blocking factor has an apparent molecular weight of ca. 150,000.